Comparative analysis examining patterns of genomic differentiation across multiple episodes of population divergence in birds. Issue 2 (15th March 2018) - Delmore, Kira E.; Lugo Ramos, Juan S.; Van Doren, Benjamin M.; Lundberg, Max; Bensch, Staffan; Irwin, Darren E.; Liedvogel, Miriam
Abstract: Heterogeneous patterns of genomic differentiation are commonly documented between closely related populations and there is considerable interest in identifying factors that contribute to their formation. These factors could include genomic features (e.g., areas of low recombination) that promote processes like linked selection (positive or purifying selection that affects linked neutral sites) at specific genomic regions. Examinations of repeatable patterns of differentiation across population pairs can provide insight into the role of these factors. Birds are well suited for this work, as genome structure is conserved across this group. Accordingly, we reestimated relative ( FST ) and absolute ( dXY ) differentiation between eight sister pairs of birds that span a broad taxonomic range using a common pipeline. Across pairs, there were modest but significant correlations in window‐based estimates of differentiation (up to 3% of variation explained for FST and 26% for dXY ), supporting a role for processes at conserved genomic features in generating heterogeneous patterns of differentiation; processes specific to each episode of population divergence likely explain the remaining variation. The role genomic features play was reinforced by linear models identifying several genomic variables (e.g., gene densities) as significant predictors of FST and dXY repeatability. FST repeatability was higher among pairs that were further along the speciation continuum (i.e., more reproductively isolated) providing further insight into how genomic differentiation changes with population divergence; early stages of speciation may be dominated by positive selection that is different between pairs but becomes integrated with processes acting according to shared genomic features as speciation proceeds.